Validation of a traditional Italian-style salami manufacturing process for control of salmonella and Listeria monocytogenes - Nightingale, K.K.; Thippareddi, H.; Phebus, Randall K.; Marsden, James L.; Nutsch, Abbey L. (My University, 2008)
Italian-style salami batter (formulated with pork shoulder) was inoculated with ca. 7.0 log CFU/g of either Salmonella or Listeria monocytogenes. Salami links (55-mm cellulose casings) were fermented at 308C for 24, 40, or 72 h and then dried to target moisture/protein ratios (MPRs) of 1.9:1 or 1.4:1. Links were sampled after fermentation (24, 40, and 72 h) and after combined fermentation-drying treatments (MPRs of 1.9:1 and 1.4:1 for all fermentation periods), and microbiological and proximate analyses were performed at each sampling. Pathogen populations were enumerated by direct plating on selective agar and by an injured-cell recovery method. When enumerated by the injured-cell recovery method, Salmonella populations were reduced by 1.2 to 2.1 log CFU/g after fermentation alone (24 to 72 h) and by 2.4 to 3.4 log CFU/g when fermentation was followed by drying. Drying to an MPR of 1.4:1 was no more effective than drying to an MPR of 1.9:1 (P . 0.05). When enumerated directly on selective media, Salmonella populations were reduced from 1.6 to 2.4 log CFU/g and from 3.6 to 4.5 log CFU/g for fermentation alone and fermentation followed by drying, respectively. L. monocytogenes populations were reduced by ,1.0 log CFU/g following all fermentation and combined fermentation-drying treatments, regardless of the enumeration method. These results suggest that the Italian-style salami manufacturing process evaluated does not adequately reduce high pathogen loads. Processors may thus need to consider supplemental measures, such as raw material specifications and a final heating step, to enhance the lethality of the overall manufacturing process.
Keywords: Validation; Salami; Salmonella; Listeria monocytogenes; Fermentation; Processed meats